ChemInform Abstract: Skeletal Transformation of α‐Pyrones Having Electron‐Withdrawing Groups at 3, 5‐Positions into Ring‐Fused Dihydrofurans. Issue 14 (March 2016) - Tanaka, Toru; Miura, Takuya; Inoue, Shoki; Iwasaki, Hiroki; Ozeki, Minoru; Kojima, Naoto; Yamashita, Masayuki
Abstract: Using dimethylsulfoxonium methylide as the methylene‐transfer reagent, various α‐pyrones are converted into dihydrofurans as major products and 1‐methylthiopyran‐1‐oxides as minor products.